Modifikasi Penggunaan Subsoil Melalui Penambahan Bahan Organik Untuk Meningkatkan Pertumbuhan Bibit Kopi Arabika (Coffea Arabica L.) - Santi Rosniawaty; Asmi Maulina; Cucu Suherman; Mochamad Arief Soleh; Rija Sudirja (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2020)
Sub soil is soil under the top soil layer, with low fertility. The use of sub soil as an Arabica coffee seedling planting media needs to be considered because the top soil layer has been much reduced by erosion or run off. Needs modification in sub-soil soils to increase fertility. Increased sub soil fertility can be done using organic materials, both solid and liquid. Coffee seedling using the right planting media will determine the growth and production of coffee in the field later. The purpose of this study was to determine the use of subsoil growing media with the addition of organic material for the growth of Arabica coffee seeds. The experiment was conducted at the Ciparanje Experimental Field, Faculty of Agriculture, Padjadjaran University, Sumedang Regency, in March to June 2019 with altitude of ± 780 meters above sea level. The experiment used a randomized block design (RBD) with 9 treatments repeated three times. The treatments are as follows: 100% topsoil; subsoil 100%; topsoil: chicken manure (2: 1); subsoil: chicken manure (1: 1); subsoil: chicken manure (2: 1); subsoil: chicken manure (3: 1); subsoil + 25% coconut water; subsoil + 50% coconut water; subsoil + 75% coconut water. The results showed that the modification of subsoil with the addition of organic matter affected the growth of Arabica coffee seedlings on stem diameter variables of 8 MST and leaf chlorophyll index of 16 MST. Subsoil media with the addition of chicken manure (3: 1) had a good effect on leaf chlorophyll index and subsoil media with 25% coconut water had a good effect on the diameter of Arabica coffee seedling stems. Subsoil can replace topsoil by adding organic matter.